2013
DOI: 10.1590/s0103-21002013000400006
|View full text |Cite
|
Sign up to set email alerts
|

Prevalência e fatores de risco independentes à tricomoníase em mulheres assistidas na atenção básica

Abstract: Objective: Evaluate the prevalence and factors associated with trichomoniasis in women receiving primary health care. Methods: A cross-sectional study was developed, involving a sample of 314 medical records, randomly selected through a process of systematic sampling, among women receiving primary health care services. The socioeconomic, demographic and clinical variables were examined. Results: The prevalence of Trichomonas vaginalis was 10.5%, and 35% of the women studied lived in rural areas. The adjusted l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
1
11

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 15 publications
0
2
1
11
Order By: Relevance
“…Other studies conducted in different States of Brazil found lower rates of this infection, 5.7% in Minas Gerais 9 , 3.56% in Sergipe 13 and 3.2% in women from São Paulo 14 . However, studies conducted in the States of Pernambuco and Goiás showed higher prevalence in comparison with this study, of 13.1% and 13.2%, respectively 4 , 23 . Characteristics such as the behavior, age, educational level, personal hygiene, access to sanitation, and the type of diagnostic methods employed, taken together, are factors that might explain the existence of different positivity rates depending on the study location.…”
Section: Discussioncontrasting
confidence: 93%
“…Other studies conducted in different States of Brazil found lower rates of this infection, 5.7% in Minas Gerais 9 , 3.56% in Sergipe 13 and 3.2% in women from São Paulo 14 . However, studies conducted in the States of Pernambuco and Goiás showed higher prevalence in comparison with this study, of 13.1% and 13.2%, respectively 4 , 23 . Characteristics such as the behavior, age, educational level, personal hygiene, access to sanitation, and the type of diagnostic methods employed, taken together, are factors that might explain the existence of different positivity rates depending on the study location.…”
Section: Discussioncontrasting
confidence: 93%
“…CARLI, 2004). Estudos recentes mostraram que a tricomoníase pode: facilitar a transmissão do vírus da imunodeficiência humana (HIV) (SORVILLO et al, 2001); causar partos prematuros e baixo peso em recém-nascidos; além de predispor a doença inflamatória pélvica atípica em mulheres, câncer cervical e infertilidade (LIMA et al, 2013).…”
Section: Conclusãounclassified
“…Quando sintomáticos podem manifestar disúria, corrimento uretral de aspecto purulento, infecção do epidídimo e próstata e dor testicular (COUTO, 2015). Nas mulheres o odor fétido e dispareunia são relatados em alguns casos, podendo ocasionar cervicite, uretrite, secreção purulenta, espumosa, amarelo esverdeada, prurido, disúria, colpitis macularis ou colo em morango (DOMEIKA et al, 2010;LIMA et al, 2013;PESSOA et al, 2012).…”
Section: Manifestações Clínicasunclassified